Development of Sr modified Al–Si–Mg–Fe based alloys for automotive components - H.R. Ammar; E. Samuel; A.M. Samuel; E. Elsharkawi; H.W. Doty; F.H. Samuel (Journal of Materials Research and Technology)
The aim of this work is to create a comprehensive database relating to the tensile properties of a eutectic Al–Si–Mg alloy. The studies reported herein cover the dissolution of the β-iron Al5FeSi phase by evaluating the effect of the iron (Fe) content, the influence of modification by strontium (Sr), and the duration of the solutionizing treatment from 0 to 200 h at 540 °C. The last step is to establish a link between the tensile properties obtained and the characteristics of the microstructures, mainly the length of the β-Al5FeSi platelets. Solution treatment at 540 °C was applied to the eutectic alloys for times of up to 200 h. Unmodified and modified Al–Si–Mg alloys with high Fe content accelerate the dissolution of β-Al5FeSi; this being due to the rejection of silicon (Si) atoms towards aluminum (Al) and resulting in transforming the β-Al5FeSi into Al6Fe. The unmodified alloy shows a maximum reduction in the length of the β-phase platelets after 30 h of solution treatment, compared to 10 h for the modified alloy. Therefore, Sr addition decreases the duration of treatment due to the initial fragmentation of platelets. The process of fragmentation/dissolution of the β-Al5FeSi phase during solution treatment at 540 °C is associated with the ductile Al matrix characterized by the formation of dimple structure. The lack of an age hardening response of the ternary Al–12%Si-0.045%Sr alloy results in low alloy strength, making this alloy unsuitable for automotive components that may be exposed to high temperatures. The results of this study were supported by extensive tensile testing (about 1000 tensile bars). The quality-index method was found to be useful in classifying the alloys according to their performance.